How Cultural Divergence Influences Expatriate’s Performance in Malaysia - Salma Sultana, Umme; Warda Andalib, Tarnima; Ridzuan Darun, Mohd (KnE Social Sciences, 2019)
Malaysia is one of the countries which welcome expatriates from all over the world to fill the need for skilled employees. This paper provides an overview of how cultural divergence influence expatriates performance in Malaysia. The main purpose of this study is to identify the important issues which directly or indirectly, positively or negatively influence expatriate’s performance in day to day work. This study reviewed 55 papers related to cultural divergence, employee performance, cultural intelligence, and human resource management practices in Malaysia. The finding highlights that expatriates experience cultural clashes between foreign and local values, which pose direct influences on expatriates’ performance. This study contributes to the body of knowledge in the cross-cultural management field as well as practical implications to expatriating firms. Finally, this research is beneficial and informative, especially for Malaysian researchers and managers in International Human Resource Management (IHRM) field.